Nutrition in kidney disease - Burrowes, Jerrilynn D.; Chertow, Glenn M.; Byham-Gray, Laura D. (Nutrition and Health, 2014)
Nutrition in Kidney Disease, Second Edition addresses  the relationships between nutrition and (1) normal kidney function and disease, (2) the progressiveness of chronic kidney disease (CKD) and strategies to prevent further compromise, and (3) the treatment and management of kidney failure especially during medical crises, such as acute kidney injury and its consequent nutritional therapies (e.g., enteral and parenteral nutrition).   Demographic patterns, trends and outcomes in the current health care systems are explored in the United States and abroad.  Disease prevention and management are presented over the entire lifespan, beginning with pregnancy, followed by infancy, childhood, adolescence, and adulthood, concluding with the elder years.  Foundations for clinical practice are established by devoting a complete section towards conducting a comprehensive nutritional assessment, comprising of anthropometric, biochemical, clinical, physical parameters and psychosocial concerns unique to the kidney disease population.  Nutritional therapy is also discussed across the spectrum of kidney disease, and pertinent aspects critical to successful management of disorders and conditions, such as bone disease, obesity, and nephrotic syndrome are explored. Nutrition in Kidney Disease, Second edition highlights cutting edge research in regards to exercise and functional outcomes, malnutrition and the inflammatory response, experimental therapies, and the use of complementary and alternative medicine, with a special emphasis on relevant preventative strategies.